The influence of plant spacing in the early stages of selection of rice (Oryza sativa L.) varieties - Torró, Isabel; Bretó, Pau; García-de-Izaguirre, Álvaro (Instituto Nacional de Investigación y Tecnología Agraria y Alimentaria (INIA), 2020)
The cultural practices of the early generations in a pedigree breeding programme may influence its success. The main objective of this study was to compare two selection environments in rice: Widely spaced planting in the field and dense planting in concrete basins. Both methods had yielded commercial varieties in the past. Two F2 populations (J and MS), derived from two crosses sharing the same female parent, were transplanted to both environments. Phenotypic traits were evaluated and their narrow sense heritabilities (h2) estimated in the F3 and in the F4 progenies of selected plants, all grown in the field. Growth potential was more apparent in the field for most traits, especially those related to yield, but broad sense heritabilities were higher in the basins for ten traits, being higher in the field for the other five. In population F2MS, field selection resulted in F3 plants which retained a higher tillering ability than those derived from basins selection. Most traits showed low h2 values: Additive variance was only relevant in panicle length (in both populations), plant height and mean panicle weight (in the J population). However, response to one generation of selection (from F3 to F4) also showed fixable variation in panicle number. In addition, this selection reduced plant height, increased culm diameter and internode length (in both populations), and improved pulling resistance (against lodging) in population J. It may be concluded that both practices can be used for selection in the F2, although different responses might be expected in yield related traits.